Simulation of electrical characterization on lateral silicon-on-insulator PIN Diode for space radiation detector - Zainudin, Z.; Ismail, Ahmad Fadzil; Hasbullah, Nurul Fadzlin; Sabri, Sharizal Fadlie (2014)
This paper discusses on the performance of SOI pin diode radiation detector when compared to conventional bulk silicon pin diode radiation detector. Lateral SOI detector was virtually fabricated in SILVACO ATHENA and its electrical characteristics was analyzed in SILVACO ATLAS. It was found that SOI pin diode produced lower leakage current value with 1x104 A/μm2 difference compared to bulk structure. However, the same SOI structure suffered from temperature variation with an increment of 1x102 A/μm2 in current density after the temperature was varied from 27°C to 80°C.